The relation between teacher and students' mathematical mindsets to the student’s comprehension of mathematics concepts - Maskar, Sugama; Herman, Tatang (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
The aim of this study is to understand the relationship between teacher and student mindsets in relation to the student’s comprehension of mathematics concepts. This study used a qualitative research type with a case study method. Participants in this study were 30 students and one teacher from one of the public junior high schools in Cianjur, Indonesia. Data sources used in this study were collected through teacher and student questionnaires, class observations, and semi-structured interviews. The class observation material was about linear function, and the learning process was carried out using the Complex Instruction (CI) approach based on growth mindset instruction. The questionnaire results show that teachers and students tend to have a fixed mindset. The fixed mindset of both the students and the teacher is particularly evident in their beliefs about the nature of math and their orientation towards student mastery and performance. The results of observations and interviews show a relationship between this mindset and student performance in class. Most students tend to show low performance in understanding linear function concepts. Based on the observations, students experienced problems in algebra thinking, had difficulty understanding mathematical concepts as a whole, and showed a lack of motivation and self-confidence. The results indicate that there is a significant relationship between the fixed mindsets of teachers and students towards students' lower performance in mathematics learning in the classroom.